2017
DOI: 10.1016/j.bbmt.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Donor-to-Recipient ABO Mismatch Does Not Impact Outcomes of Allogeneic Hematopoietic Cell Transplantation Regardless of Graft Source

Abstract: The impact of ABO mismatch has been studied on various hematopoietic cell transplant (HCT) outcomes including neutrophil and platelet engraftment, pure red cell aplasia (PRCA), acute and chronic GVHD, non-relapse mortality (NRM) and overall survival (OS). Yet conflicting results have been reported. However, the impact of ABO mismatch on transplant outcomes with various graft types has not been carefully investigated. We analyzed the impact of various graft sources and type of ABO mismatch on transplant outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…Ozkurt et al reported more frequent severe aGVHD among minor ABO-mismatched patients [32], but Kimura et al found a high incidence of severe aGVHD in both major and minor ABO mismatches [33]. There were also conflicting results that failed to find a difference in rates of aGVHD between minor ABO incompatibility and others [3436]. No evidence of an association between the ABO mismatch and cGVHD or survival was observed in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Ozkurt et al reported more frequent severe aGVHD among minor ABO-mismatched patients [32], but Kimura et al found a high incidence of severe aGVHD in both major and minor ABO mismatches [33]. There were also conflicting results that failed to find a difference in rates of aGVHD between minor ABO incompatibility and others [3436]. No evidence of an association between the ABO mismatch and cGVHD or survival was observed in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Conversely, the association of ABO matching with OS has not been previously reported in UCBT to our knowledge, but previous studies included none or only few DUCB transplants. [28][29][30] In the present analysis, ABO matching remained a significant risk factor for OS after adjusting for potential confounders, although it is important to note that its effect size was small with borderline significance. We also looked at the influence of interunit ABO match on survival but did not find any association.…”
Section: Discussionmentioning
confidence: 52%
“… 29 This finding was subsequently confirmed in the haploidentical setting. 7 In contrast, Damodar et al 5 reported no effect of ABO-mismatch on aGVHD and survival of 1502 patients analyzed by graft sources. Regarding our patients, we failed to observe any effect of ABO mismatch on aGVHD so that the higher NRM in our series conceivably relies on other causes.…”
Section: Discussionmentioning
confidence: 97%